Influence of Water Quality on Distribution Patterns and Diversity of Enteromius Fish Species in Small Water Bodies of Uasin Gishu County, Kenya - Jepleting, Hildah; Mulei, Josephine; Chemoiwa, Emily J.; Barasa, James; Wanga, James; Saina, Christopher (African Journal of Education,Science and Technology (AJEST), 2022)
The Enteromius species are a widely distributed group of freshwater fishes in Africa. However, their abundance and diversity are affected by environmental quality. This study therefore investigated the relationship between water quality variables and Enteromius assemblages in eight (8) small water bodies in Uasin Gishu County, Kenya. Selected insitu and lab analyzed physico-chemical water quality variables were determined across the reservoirs. Fish species were also collected from the different reservoirs for identification and enumeration. All the determined variables; temperature, dissolved oxygen, total dissolved solids, total suspended solids, salinity, pH, conductivity, turbidity, ammonia, nitrites, nitrates, total phosphorous, and total nitrogen were significantly different (p < 0.05) across the reservoirs. A total of 756 fish individuals from five species; Enteromius apleurogramma, Enteromius cercops, Enteromius neumayeri, Enteromius paludinosas, and Enteromius yongei were recorded. Enteromius neumayeri was the most abundant while Enteromius yongei recorded the least abundance with only 19 individuals. Fish abundance and diversity was significantly different across the reservoirs. Species richness differed among the reservoirs with Chebara recording the highest number of taxa (3 taxa) while Chepkosom, Ellegrin, Kerita and Kesses recording one taxa each. All the sampled Enteromius fish species had negative allometric growth (b < 3, t-test, p < 0.05). Nonetheless, they were all in good growth condition (Kn > 1). The differences in species diversity and richness in the study can be attributed to variation in the tolerance level of environmental degradation due to anthropogenic impacts observed. Biodiversity is important for the future sustainability of natural resources that include commercial fisheries. Fish species distribution is also an important indicator of ecological health as the abundance and health of fish indicate the health of the water bodies. Given that there was no single reservoir that supported all the Enteromius fish diversity in healthy and sustainable populations, conservation and protection of all the reservoirs in Uasin Gishu is crucial.